Galen’s Nachlass in Slavonic Intellectual Landscapes: Knowledge Transmission in the Byzantine Commonwealth - Geller, Florentina Badalanova (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2023)
The current publication offers the first English translation of a cluster of medieval and early modern Slavonic renditions of Byzantine Greek editions of ancient medical compositions, the authorship of which is attributed to Galen. Among the emblematic texts deserving special attention are his celebrated commentaries on the Corpus Hippocraticum, the direct Greek Vorlage of which remains unidentified. The Slavonic translations of these Galenic paraphrases refer to various medical conditions as well as human anatomy and physiology; they contain discussions on diagnosis, therapeutics, and health care (including dietetics), as well as astral medicine (e.g., calendrical templates of recommended procedures according to the zodiac, winter and summer solstices, autumn and vernal equinoxes, lunar phases, the position of the Pleiades). While the earliest extant Slavonic manuscript witnesses are dated to the first quarter of the 15th century, their protographs must have originated much earlier among the cloistral scriptoria of Mt Athos and further disseminated through monastic networks within the Byzantine Commonwealth, from the Balkans to Russia. These texts represent a small but important contribution to the reception history of Galenic heritage within the Slavonic world, which has hardly been recognized.